EVALUATION OF THE EFFICIENCY OF ANTIRESORPTIVE THERAPY FOR OSTEOPOROSIS IN MULTIPAROUS WOMEN - I.G. MUKHAMEDOVA; A.A. RAZZOKOV; A S. EKHSONOV (Avicenna Tajik State Medical University, 2019)
Objective: To study the results of long continuous comprehensive treatment of osteoporosis in multiparous women on the background degenerative and dystrophic skeletal changes in the postmenopausal period. Methods: A retrospective analysis of the results of treatment of 53 multiparous women on the background of degenerative and dystrophic skeletal changes in the postmenopausal period assessment in the dynamics of the level of Ca and Mg in serum, bone mineral density in the vertebral segment and proximal hip. Results: It was found that after 3-6-18 months of treatment in 41 (77.4%) pain relief was observed, in 38 (71.1%) of serum calcium and magnesium increased in the case. X-ray showed marked increased clarity of the contours of the bones of the skeleton and an increase in bone mineral density (BMD) at the level of the vertebral segment by 7.4% (р<0.001) and in the proximal hip 3.6% (p<0.05). Conclusion: The results of the study show that long continuous intake of antiresorptive drugs contributes to the activation of the process of bone remodeling, prevent further bone loss and achieve non-osteoporotic T-criterion values